2018
DOI: 10.3390/ijms19020504
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Alteration of Human T Cells Exposed Continuously to Asbestos

Abstract: Asbestos is a known carcinogen and exposure can lead to lung cancer and malignant mesothelioma. To examine the effects of asbestos fibers on human immune cells, the human T cell leukemia/lymphoma virus (HTLV)-1 immortalized human T cell line MT-2 was employed. Following continuous exposure to asbestos fibers for more than eight months, MT-2 sublines showed acquisition of resistance to asbestos-induced apoptosis with decreased death signals and increased surviving signals. These sublines showed various characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 55 publications
(91 reference statements)
1
12
0
1
Order By: Relevance
“…In another aspect, the effects of asbestos fibers on various human immune cells such as CTL, NK cells, Tresp, and Treg indicated that asbestos exposure reduced the antitumor immunity [55]. This may involve in tumor occurrences and rapid progression of asbestos-induced cancers such as malignant mesothelioma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another aspect, the effects of asbestos fibers on various human immune cells such as CTL, NK cells, Tresp, and Treg indicated that asbestos exposure reduced the antitumor immunity [55]. This may involve in tumor occurrences and rapid progression of asbestos-induced cancers such as malignant mesothelioma.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was found that matrix metalloproteinase (MMP)-7 gene expression was enhanced in asbestos-exposed subline rather than original line [55]. Although the role of this finding is not explored well, MMP-7 also known as matrilysin is considered as the enzyme related to the cancer metastasis and invasion to cut extracellular matrix such as proteoglycan, fibronectin, and collagen type IV [56].…”
Section: The Effects Of Silica and Asbestos On Treg Silica Induces Ementioning
confidence: 99%
“…All findings described in this chapter are summarized in Figure 1. In this review, the effects of silica [67][68][69] and asbestos [64][65][66] are introduced and discussed. However, people are exposed to many more potentially hazardous occupational and environmental substances, such as various materials in air pollutants and a variety of metals in work environments.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, continuous and low-dose exposure to asbestos caused a reduction in antitumor immunity in CTLs, NK cells, CD4+ T cells, and Tregs [64][65][66]. Thus, it could be considered that people subjected to continuous, low-dose exposure to asbestos are susceptible to the onset of cancers because of a gradual reduction in antitumor immunity.…”
Section: Asbestos and Antitumor Immunitymentioning
confidence: 99%
See 1 more Smart Citation